2018
DOI: 10.1088/1752-7163/aacbfb
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivoemission of volatile organic compounds from gastric cancer and non-cancerous tissue

Abstract: The presence of certain volatile organic compounds (VOCs) in the breath of patients with gastric cancer has been reported by a number of research groups; however, the source of these compounds remains controversial. Comparison of VOCs emitted from gastric cancer tissue to those emitted from non-cancerous tissue would help in understanding which of the VOCs are associated with gastric cancer and provide a deeper knowledge on their generation. Gas chromatography with mass spectrometric detection (GC-MS) coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 82 publications
1
28
0
Order By: Relevance
“…Nonetheless, despite the large surface for capturing VOCs, monotrap has been used solely for static sampling. This means that improving the preconcentration technique (e.g., NTME; needle trap extraction and ITEX; in tube extraction) requires shorter incubation time but generates better intensity (Mochalski et al, 2018 ) and should be applicable to single cell studies as well (Serasanambati et al, 2019 ). For this reason, we developed an active sampling approach for monotrap-based sample preparation which is suitable for cellular VOC analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, despite the large surface for capturing VOCs, monotrap has been used solely for static sampling. This means that improving the preconcentration technique (e.g., NTME; needle trap extraction and ITEX; in tube extraction) requires shorter incubation time but generates better intensity (Mochalski et al, 2018 ) and should be applicable to single cell studies as well (Serasanambati et al, 2019 ). For this reason, we developed an active sampling approach for monotrap-based sample preparation which is suitable for cellular VOC analysis.…”
Section: Introductionmentioning
confidence: 99%
“…CAN_1 variable markedly separated Y from the other three groups and the discriminant VOCs involved were 2-butanone, isopropyl alcohol, 2-pentanone, 3penten-1-ol, and pyrrole. These VOCs were detected in the urine of healthy subjects but also, in some cases with higher levels, in patients with different pathologies, such as cancer, nephropathy, and metabolic disorders (Silva et al 2012;Wang et al 2017;Mochalski et al 2018;Jia et al 2019). In our samples, these VOCs were more associated with Y group as they showed a higher correlation with CAN1.…”
Section: Discriminant Analysis Of Urinesmentioning
confidence: 48%
“…Some of these have been already reported in the literature, namely acetic acid was found as a discriminant when associated with controls (CTL) in a study conducted by Ahmed et al 20 that investigated the possibility of faecal VOMs as potential diagnostic biomarkers for inflammatory bowel disease. Mochalski et al 21 investigated the emission of volatile compounds from gastric cancer tissues and non-cancerous tissues with the aim of identifying characteristic chemical patterns associated with gastric cancer. Furthermore, Silva et al 10,12 also reported phenols as the major chemical family identified in urine from the oncologic group.…”
Section: Resultsmentioning
confidence: 99%